2012
DOI: 10.1111/j.1365-2044.2012.07075.x
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Airway Society Guidelines for the management of tracheal extubation

Abstract: SummaryTracheal extubation is a high‐risk phase of anaesthesia. The majority of problems that occur during extubation and emergence are of a minor nature, but a small and significant number may result in injury or death. The need for a strategy incorporating extubation is mentioned in several international airway management guidelines, but the subject is not discussed in detail, and the emphasis has been on extubation of the patient with a difficult airway. The Difficult Airway Society has developed guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(155 citation statements)
references
References 183 publications
2
139
2
6
Order By: Relevance
“…Endotracheal extubation is a critical step during postoperative care in neurosurgical patients 9. Pain is common during the extubation period, and is related to complications and adverse outcomes 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endotracheal extubation is a critical step during postoperative care in neurosurgical patients 9. Pain is common during the extubation period, and is related to complications and adverse outcomes 8.…”
Section: Discussionmentioning
confidence: 99%
“…By using the patient's self-report pain scale as the pain evaluation method, Gacouin et al 8 found that 45% of patients experienced severe pain at the time of endotracheal extubation. Acute pain during extubation is associated with sympathetic nervous system activation, which could result in respiratory and circulatory instability 9. Therefore, it is reasonable to control pain and stress responses at the time of endotracheal extubation in some high-risk patients, such as those after intracranial surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Following the guideline of Difficult Airway Society Extubation Guidelines Group [7], the patients were ready for scheduled extubation after tolerating a spontaneous breathing trial in ICU. The decision to extubate was at the discretion of the treating doctors in ICU and no mandatory extubation variables were set.…”
Section: Methodsmentioning
confidence: 99%
“…The use of a peripheral nerve stimulator to ensure a train-of-four ratio of 0.9 or above is recommended in order to reduce the incidence of postoperative airway complications [55].…”
Section: What Do the Guidelines Say?mentioning
confidence: 99%